2021
DOI: 10.1097/pai.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear EGFR Expression Is Associated With Poor Survival in Laryngeal Carcinoma

Abstract: The membrane EGFR (mEGFR) protein over-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…A correlation between nuclear EGFR expression and HNSCC clinical parameters has also been reported by several authors. In a study on laryngeal HNSCC, a higher frequency of strong nuclear EGFR was found in invasive tumors compared to laryngeal dysplasia and vocal cord polyps, and high nuclear EGFR expression levels correlated with worse overall cancer patients’ survival ( 39 ). In oropharyngeal HNSCC high nuclear EGFR expression levels were associated with reduced responses to radiation therapy, higher risk of local recurrence and lower overall survival ( 99 , 100 ).…”
Section: Involvement Of Non-canonical Erbb Signaling In Hnsccmentioning
confidence: 99%
“…A correlation between nuclear EGFR expression and HNSCC clinical parameters has also been reported by several authors. In a study on laryngeal HNSCC, a higher frequency of strong nuclear EGFR was found in invasive tumors compared to laryngeal dysplasia and vocal cord polyps, and high nuclear EGFR expression levels correlated with worse overall cancer patients’ survival ( 39 ). In oropharyngeal HNSCC high nuclear EGFR expression levels were associated with reduced responses to radiation therapy, higher risk of local recurrence and lower overall survival ( 99 , 100 ).…”
Section: Involvement Of Non-canonical Erbb Signaling In Hnsccmentioning
confidence: 99%
“…For head and neck tumors, numerous diagnostic and prognostic markers have been investigated in clinical studies, but their clinical significance remains questionable [ 5 , 22 ]. Recent discoveries related to a completely new way of regulating cell proliferation and apoptosis through the independent action of EGFR in the nucleus of numerous tumors, such as ovarian, breast, oropharyngeal, laryngeal, and esophageal carcinoma, have been the basis for studying premalignant and malignant changes in the oral cavity, where the role of this receptor had not been previously elucidated [ 8 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition to nEGFR, we also analyzed the expression of markers of cell cycle and proliferation (Ki-67, cyclin D1, p53, mEGFR) and markers of tumor stem cells (ABCG2) involved in oral carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that EGF, H2O2, UV radiation, therapeutic agents, and ionizing radiation may cause translocation of EGFR to the nucleus, where nuclear EGFR (nEGFR) interacts with various transcription factors (cyclin D1, ABCG2/BCRP, Aurora kinase A, COX-2, gene regulator c-Myc, iNOS) and acts on the activation of numerous genes involved in cell proliferation, tumor progression, and DNA repair [ 7 , 8 , 9 , 10 ]. Available literature indicates that overexpression of nEGFR in ovarian, breast, oropharyngeal, laryngeal, and esophageal cancers negatively affects disease prognosis and resistance to radiotherapy and chemotherapy, whereas its role in oral malignancies has not yet been investigated [ 8 , 11 , 12 , 13 , 14 , 15 , 16 ]. The above only confirms the complexity and scope of the network of signaling pathways mediated by EGFR activation that play an important role in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…18,30,31 However, the particular attention of scientists has been attracted by its overexpression in tumor tissues of the ovary, breast, larynx, oropharyngeal carcinoma, and squamous cell carcinoma of the esophagus, where it has been shown to negatively affect survival. 18,22,[32][33][34] Taguchi found nEGFR expression in 28% of patients with tongue squamous cell carcinoma, but without correlation with clinicopathologic factors. 35 The effect of nEGFR expression in OPMD and OSCC in other areas of the oral cavity has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…nEGFR is expressed in many healthy tissues, where it is involved in the regulation of transcription, cell proliferation, replication, and DNA repair 18,30,31 . However, the particular attention of scientists has been attracted by its overexpression in tumor tissues of the ovary, breast, larynx, oropharyngeal carcinoma, and squamous cell carcinoma of the esophagus, where it has been shown to negatively affect survival 18,22,32–34 . Taguchi found nEGFR expression in 28% of patients with tongue squamous cell carcinoma, but without correlation with clinicopathologic factors 35 .…”
Section: Discussionmentioning
confidence: 99%